Les droits de la personne et la politique étrangère canadienne : le cas de l’Indonésie - Nossal, Kim (Études internationales, 1980)
Margaret Doxey has argued that there exists a "rhetoric gap" between the lofty pronouncements of Canadian governments on the question of human rights violations by other governments in the international System and the actions of the Canadian government. This paper argues that specific external constraints will hamper any attempt by governments in Ottawa to transform the rhetoric of official statements into direct policy action. This paper examines Indonesian-Canadian relations during the 1970s as a case study, and concludes that economic, strategic and diplomatic imperatives and interests proved more compelling than concerns over the treatment of political prisoners by the government of General Suharto, or concerns over the Indonesian invasion of Timor. The specific case study suggests a more general observation about human rights and Canadian foreign policy : that where trade-offs must be made, economic and diplomatic interests will tend to prevail over concerns about human rights violations.